2023
DOI: 10.1038/s41598-023-28292-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a treatment for water contaminated with Cr (VI) using cellulose xanthogenate from E. crassipes on a pilot scale

Abstract: Water care is an imperative duty in industries with effluents loaded with pollutants such as heavy metals, especially chromium (VI), extremely dangerous for humans and the environment. One way of treating water is possible through a continuous system with dry and crushed vegetable biomass of cellulose xanthogenate because it can adsorb heavy metals, especially due to its low production costs. Through continuous systems and with the waste of PET plastics, it is possible to develop a water treatment process adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…As a result of this adjustment, we can use Model (1) for adsorption capacities. For comparison, we also used Carreño's model (2) and found that the adsorption capacities for Cr (VI) and Pb (II) were 10 mg/g and 18 mg/g, respectively. Equations ( 1) and ( 2) relate the volume of water to the amount of biomass used.…”
Section: Results Of Adsorptions Of Cr (Vi) and Pb (Ii)mentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of this adjustment, we can use Model (1) for adsorption capacities. For comparison, we also used Carreño's model (2) and found that the adsorption capacities for Cr (VI) and Pb (II) were 10 mg/g and 18 mg/g, respectively. Equations ( 1) and ( 2) relate the volume of water to the amount of biomass used.…”
Section: Results Of Adsorptions Of Cr (Vi) and Pb (Ii)mentioning
confidence: 99%
“…The model is correlated with the Langmuir isotherm. The Carreño model is used to determine the design parameters of this type of system [1][2][3][4][5], in the Table 1, is the Adsorption models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of hydroxyl (OH) and carboxylic (COOH) groups in cellulose leads to the removal of heavy metals by adsorption through cation exchange or chemical mechanisms [17,18]. This cellulose is found in considerable amounts within the aquatic plant E. crassipes [19][20][21][22], which is abundant in tropical environments due to its dry biomass resulting from regular cleaning in the wetlands, lagoons, and rivers of Bogotá D.C. [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The biomass of E. crassipes, without any modification, could treat around 2 L of this same water[1], but with the addition of PPT better yields of up to more than two liters more water could be achieved. The addition of chemical agents to this type of biomass also improved the treatment yields, such is the case of the xanthate biomass of E. crassipes, where around 3.5 L of contaminated water was treated under the same concentrations[20]. The addition of PPT achieved better yields due to the expansion of active sites in the EC biomass[29][30][31].Analysis of Reliability.…”
mentioning
confidence: 99%